The G protein subunit α1, CaGα1, mediates ethylene sensing of mango anthracnose pathogen Colletotrichum asianum to regulate fungal development and virulence and mediates surface sensing for spore germination - Kao, Chao-Yang; Wu, Chun-Ta; Lin, Hsien-Che; Hsieh, Dai-Keng; Lin, Huey-Ling; Lee, Miin-Huey (Frontiers in Microbiology, 2022)
Mango is an important tropic fruit, but its production is highly restricted by anthracnose diseases. Mango anthracnose development is related to the fruit-ripening hormone ethylene, but how the pathogen senses ethylene and affects the infection remains largely unknown. In this study, mango pathogen Colletotrichum asianum strain TYC-2 was shown to sense ethylene to enhance spore germination, appressorium formation and virulence. Upon further analysis of ethylene sensing signaling, three histidine kinase genes (CaHKs) and a G-protein gene (CaGα1) were functionally characterized. Ethylene upregulated the expression of the three CaHKs but had no influence on CaGα1 expression. No function in ethylene sensing was identified for the three CaHKs. Ethylene enhanced spore germination and multiple appressorium formation of the wild-type TYC-2 but not CaGα1 mutants. TYC-2 has extremely low germination in water, where self-inhibition may play a role in ethylene sensing via CaGα1 signaling. Self-inhibitors extracted from TYC-2 inhibited spore germination of TYC-2 and CaGα1 mutants, but ethylene could not rescue the inhibition, indicating that the self-inhibition was not mediated by CaGα1 and had no interactions with ethylene. Interestingly, spore germination of CaGα1 mutants was significantly enhanced in water on hydrophobic but not hydrophilic surfaces, suggesting that CaGα1 is involved in surface sensing. In the pathogenicity assay, CaGα1 mutants showed less virulence with delayed germination and little appressorium formation at early infection on mango leaves and fruit. Transcriptome and qRT‒PCR analyses identified several pathogenicity-related genes regulated by ethylene, indicating that ethylene may regulate TYC-2 virulence partially by regulating the expression of these genes.